Implementation of the INTERGROWTH‐21st Project in China. Issue 9 (17th May 2013) - Pan, Y; Wu, MH; Wang, JH; Pang, RY; Knight, HE; Cheikh Ismail, L; ,
Abstract : Please cite this paper as: Pan Y, Wu M, Wang J, Pang R, Knight H, Cheikh Ismail L, for the International Fetal and Newborn Growth Consortium for the 21 st Century (INTERGROWTH‐21 st ). Implementation of the INTERGROWTH‐21 st Project in China. BJOG 2013; 120 (Suppl. 2): 87–93. The East Asian site in the INTERGROWTH‐21 st Project was Shunyi County, Beijing, China, which is an affluent suburb of north Beijing delivering approximately 7000 women annually. The Newborn Cross‐Sectional Study (NCSS) sample was drawn from two hospitals, covering >85% of births in the county. The Fetal Growth Longitudinal Study sample (FGLS) was recruited from the antenatal clinic of Shunyi Maternal & Child Health Hospital, the larger of the two institutions. Special activities to promote the study in this population included: (1) the distribution of health education materials about the importance of antenatal care and (2) the organisation of seminars by the study team to brief key stakeholders at the two hospitals about the goals of the research. One of the major challenges at this site in the early stages of the study was a reluctance to have an early ultrasound dating scan (<14 +0 weeks of gestation). This challenge was overcome after a thorough evaluation of the literature regarding the benefits of an early ultrasound scan for dating purposes, as a result of which there was a formal change in hospital policy.